Strategi Komunikasi Pemasaran Gayo Camping Ground Terhadap Upaya Meningkatkan Pengunjung Wisata Ke Danau Laut Tawar - Harahap, Viana Safrida; AB, Subhan; Mahendra, Mahesy (Telangke:Jurnal Telangke Ilmu Komunikasi, 2024)
This thesis is entitled "Gayo Camping Ground Marketing Communication Strategy for Efforts to Increase Tourism Visitors to Lake Laut Tawar" This type of research is descriptive qualitative research. The problems examined in this thesis are about how the Gayo Camping Ground marketing communication strategy is in an effort to increase tourist visitors to Lake Laut Tawar and how are the communication barriers for the Gayo Camping Ground tour crew. Data collection techniques are carried out by observation, interviews, and documentation. This research was carried out at Pante Ujung Mepar and the Gayo Camping Ground Office for one month, from June to July. The results of this study indicate that Gayo Camping Ground in increasing visitors uses the marketing mix theory from Kotler and Keller which consists of product, price, place, promotion, and person, and shows the beginnings of Gayo Camping Ground tourism in Central Aceh which initiated by Satria Darmawan. Gayo Camping Ground's marketing strategy, according to the researcher's analysis, is very good because implementing promotions via Instagram and Tiktok is in fact very effective in increasing the number of new customers (visitors). In this study there were six informants as data sources. Communication barriers at Internal Gayo Camping Ground show ineffective delivery and response from leaders to crew accompanied by certain factors such as noise, lack of concentration and also poor delivery.